Adopsi Kode Etik Internasional AAOIFI bagi Akuntan Islam Indonesia - R. Ibnu Haitam; Misnen Ardiansyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Various accounting scandals, financial cases and unethical practices violating laws and standards still occur today in Indonesia. Indonesia's code of ethics for Islamic accounting needs to be formulated in line with the development of sharia accounting practices that are widespread in the world of Islamic banking and Indonesia's dynamic sharia economy with high complexity. Indonesia's Islamic sharia accounting code of ethics needs to adopt a code of ethics compiled by international experts in the global Islamic accountant organization AAOIFI as a drafting reference. The research uses an interactive qualitative type that advances interview techniques to collect data from scholars. The primary source of research uses the code of ethics issued by AAOIFI and through interviews with Islamic accounting expert from IAI and ulama (scholars) in the Indonesian Ulema Council (MUI). The principles of the AAOIFI code of ethics include taqwa, tawakal, amanah, sidiq. quwwah and tawasi bil haq. The adoption of a code of ethics for Indonesian Islamic accountants is an important matter of duplicating the virtues in modern applicants, namely applying Islamic law in order to provide solutions and guidance in contemporary modern problems. The preparation of a code of ethics for Indonesian Islamic accountants requires the Islamic accountant profession in the complex modern world needs to pay attention to urf am and urf khas so that it will give great benefits because until now the Indonesian Islamic accountant profession does not have a professional code of ethics. Keywords: Islamic Accounting, Code of Ethics, Accountants